The research on poetry therapy: analyzing the function and capacities of Persian poetry - Manijeh Firoozi; Elahe Karimi Riabi (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
Poetry therapy is a method by harmonic reading poems, individually or in group manner, which aims to focus on metaphorical images in poetry and to get a deep meaning in the text of the poem. This pleasant method has capabilities that can be a good alternative in cases where rigid psychotherapies do not be effective. For this reason, an attempt was made to study in this field in order to study its position in Farsi and English language articles. The English keywords poetry therapy, writing therapy, poem therapy and its Persian equivalent were searched and after initial screening. The findings showed that poetry therapy has been used for psychological, medical and neuroscience area. The research method in research cases were quantitative (experimental and semi-experimental studies), qualitative (case studies) and mixed (analysis of participants' poems and group exercises), individually and in groups, but in most cases in groups. In order for the sessions to have validity and reliability, some structured patterns were set for the sessions that were introduced in this study. In addition to, the situation of poetry therapy in Iran was studied. Finally, the capabilities of poetry therapy in Iran were discussed.